Intellect as distinct from Openness: Differences revealed by fMRI of working memory - DeYoung, Colin G. (2009)
Relatively little is known about the neural bases of the Big Five personality trait Openness/Intellect. This trait is composed of two related but separable aspects, Openness to Experience and Intellect. On the basis of previous behavioral research (DeYoung, Peterson, & Higgins, 2005), we hypothesized that brain activity supporting working memory (WM) would be related to Intellect but not Openness. To test this hypothesis we used fMRI to scan a sample of 104 healthy adults, as they performed a difficult WM task. Intellect (and not Openness) was found to correlate with WM accuracy and with accuracy-related brain activity, in left lateral anterior prefrontal cortex and posterior medial frontal cortex. Neural activity in these regions mediated the association between Intellect and WM performance, implicating these regions in the neural substrate of Intellect. Intellect was also correlated significantly with scores on tests of intelligence and working memory capacity, but the association of Intellect with brain activity could not be entirely explained by cognitive ability.